Survival-adjusted FEV1 and BMI percentiles for patients with cystic fibrosis before the era of triple CFTR modulator therapy in Germany - Dittrich, A. Susanne; Dumke, Markus; Kapl, Ferdinand; Schneider, Philipp; Wege, Sabine; Gräber, Simon Y.; Stahl, Mirjam; Herth, Felix; Nährlich, Lutz; Mall, Marcus A.; Sommerburg, Olaf (Respiration, 2023)
Background: Pulmonary disease is the major cause for morbidity and mortality in cystic fibrosis (CF). In CF, forced expiratory volume in 1 s (FEV1) referenced against a healthy population (FEV1%predicted) and body mass index (BMI) do not allow for the comparison of disease severity across age and gender. Objectives: We aimed to determine updated FEV1 and BMI percentiles for patients with CF and to study their dependence on mortality attrition. Methods: Age- and height-adjusted FEV1 and BMI percentiles for CF patients aged 6-50 years were calculated from 4,947 patients of the German CF Registry for the period 2016-2019 utilizing quantile regression and a Generalized Additive Model for Location, Scale and Shape (GAMLSS). Further, survival-adjusted percentiles were estimated. Results: In patients with CF, FEV1 increased throughout childhood until maximal median values at 16 years in females (2.46 L) and 18 years in males (3.27 L). During adulthood, FEV1 decreased substantially. At 17 years of age, the 25th BMI percentile of patients with CF (females 18.50 and males 18.15 kg/m2) was below the 10th BMI percentile of the German reference cohort. From the age of 20 years, survival (96.3%) decreased tremendously. At 50 years of age (survival 15.0%), the 50th CF-specific FEV1 or BMI percentile among the survivors corresponded to the 92.5th percentile among the total CF birth cohort. Conclusions: Continuously updated disease-specific FEV1 and BMI percentiles with correction for survival may serve as age-independent measure of disease severity in CF (accessible via https://cfpercentiles.statup.solutions).
Online veröffentlicht: 14. April 2023
Gesehen am 14.08.2023